Mesh-free Dynamic Analyses of FGM Sandwich Plates Resting on A Pasternak Elastic Foundation - Rasool Moradi-dastjerdi; Hamed Momeni-Khabisi; Ramin Baghbani (Mechanics of Advanced Composite Structures)
This study analyzes the free vibration, forced vibration, resonance, and stress wave propagation of orthotropic sandwich plates made of functionally graded materials (FGMs). Dynamic analyses are conducted using a mesh-free method based on first-order shear deformation theory and the shape functions constructed using moving least squares approximation. The sandwich plates are rested on a Pasternak elastic foundation and subjected to periodic or impact loading and essential boundary conditions, which are imposed through a transfer function method. The sandwich plates are assumed to be composed of a homogeneous orthotropic core and two orthotropic FGM face sheets made of two orthotropic materials. The volume fractions of the materials are varied smoothly along the thickness of the face sheets. The convergence and accuracy of the applied method are demonstrated, after which numerical analyses are conducted to investigate the effects of elastic foundation coefficients, material distributions, geometrical dimensions, time-dependent loading, and boundary conditions on the vibrational and dynamic characteristics of the orthotropic FGM sandwich plates.